The association between Hb levels in placenta previa patients with apgar scores - Nurrahma, Herlin Ajeng; Nur Intan, Yulice Soraya; Meliala, Andreanita; Narwidina, Paramita (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2022)
Hemoglobin (Hb) level is a biochemical indicator of the nutritional status of pregnant women, and a low Hb level reduces blood supply to the placenta, which influences the incidence of placenta previa. A placenta previa develops in the lower portion of the uterus, completely or partially expanding to cover the entire birth canal and the internal uterine ostium. The APGAR score is commonly used as a predictor of infant mortality and long-term disability and as an indicator of infant health at birth. The risk of maternal and infant mortality and morbidity increases in placenta previa patients with inadequate vascularization, which can be caused by low Hb levels. This study aimed to determine the relationship between Hb levels and APGAR scores in patients with placenta previa at Sultan Agung Islamic Hospital in Semarang. This analytic observation study is a cross-sectional analysis with purposive sampling method. From January 2017 to January 2018, all placenta previa patients hospitalized at Sultan Agung Hospital in Semarang were included in this study. In this study, we used subject data that met the criteria for inclusion. The p-value derived from the chi-square analysis is 0.041 (p< 0.05). A test of association was conducted. This test revealed that the OR was 11.5 (OR > 1). Low Hb levels (11 g/dl) could significantly increase the risk of a lower APGAR score at 5 min in patients with placenta previa who have a low Hb level.